Figures 113–118 in Revisiting Potter Cove, King George Island, Antarctica, 12 years later: new observations of marine benthic diatoms ... - Al-Handal, Adil Y.; Torstensson, Anders; Wulff, Angela (Zenodo, 2022)
Figures 113–118: SEM images of the marine benthic diatoms in Potter Cove, King George Island, Antarctica, summer 2015. (113, 114) Cocconeis orbicularis, external and internal faces of sternum valve. (115, 116) Fragilariopsis cylindrus, internal valve sides. (117) Entomoneis paludosa. (118) Nitzschia australis. ... : Published as part of Al-Handal, Adil Y., Torstensson, Anders & Wulff, Angela, 2022, Revisiting Potter Cove, King George Island, Antarctica, 12 years later: new observations of marine benthic diatoms, pp. 81-103 in Botanica Marina (Warsaw, Poland) 65 (2) on page 97, DOI: 10.1515/bot-2021-0066, http://zenodo.org/record/11000147 ...